Situational Contexts of Rural Violence: a Comparison of Male and Female Perpetration - Rennison, Callie Marie (Journal of contemporary criminal justice, 2017)
The amount of social scientific knowledge about rural violence pales in comparison with that of urban violence, and even less is known about the situational contexts of rural violence. Using National Crime Victimization Survey data, we explore situational contexts of rural violence in general, as well as compare male- and female-perpetrated violence contexts. Results indicate that the contexts of violence committed by females are characterized by main effects (i.e., no weapons, no injuries across a variety of contexts), while male-perpetrated violence is highly contextual. An important finding emerged from studying contexts associated with male offenders and female victims—in every dominant context with one exception, male perpetrators were engaged in woman abuse. These findings highlight the need for greater attention to rural violence and variation in how this violence is perpetrated.